Self-report of the perception of stress and signs of bruxism generated during the pandemic in student of the health area = Autoinforme de la percepción de estrés y signos de bruxismo derivados de la pandemia en estudiantes del área de la salud - Martínez Hernández, Margarita Mahetzi
Bruxism is the repetitive muscle-mandibular behavior characterized by clenching and/or grinding of the teeth, which reflects the presence of one or more underlying conditions or factors. The objective of this descriptive study was to determine the association between bruxism and stress self-perceived during the pandemic, as well as their frequency by gender and academic area. An interrogation and self-perceived stress scale PSS-14 were applied to students from the different areas of the Institute of Health Sciences (ICSa) to determine the presence or absence of stress and bruxism symptom, a Chi-square was used for the comparison between variables, considering a value of p<0.005 as significant, a two-way ANOVA was performed to evaluate the difference between the symptoms before and during the isolation of the pandemic. The total number of participants was 825, a final sample of 420 students was obtained, made up of 297 (70.72%) women and 123 (29.28%) men, with an average age of 20±1.75 years. We found an association between the frequency of bruxism and severe stress generated during the social isolation of the COVID-19 pandemic, with a high perception of stress in the medicine area and a high frequency of bruxism in the area of nutrition p>0.005. ICSa students between 18 and 24 age perceive symptoms of bruxism and high levels of stress caused during the pandemic.